TOURISM VILLAGE DEVELOPMENT DURING THE COVID-19 PANDEMIC CASE STUDY IN TEGALWANGI VILLAGE TOURISM VILLAGE DEVELOPMENT DURING THE COVID-19 PANDEMIC CASE STUDY IN TEGALWANGI VILLAGE - Muhamammad Hiqbal Pratama; Fitri Dian Perwitasari; Devi Yuliananda; Freddy Wicaksono; Bastoni; Bayu Arisandi (Jurnal Abdisci, 2024)
Students of Universitas Muhammadiyah Cirebon must take part in Student Work Lectures (KKM) as a form of their service to the community. One of the tasks of KKM group 23 in Tegalwangi village is to create a podcast that incorporates the Ngobras (Informal conversation) program about the tourist village. Chatting, talking, or talking casually is the definition of "ngobras". The theme of Ngobras was "A thriving tourist village in the era of industrial revolution 4.0", and the resource person was Mr. H. Nana Mulyana, head of the Cirebon Regency Disbudparpora. The purpose of the KKM "Ngobras" activity is to gather information about what needs to be prepared, considered, and developed by Tegalwangi village as a tourism village.  The research location is Tegalwangi Village, Weru Subdistrict, Cirebon Regency, and descriptive methods are used. The results of this Ngobras KKM activity provide some input for Tegal Wangi Village to develop a tourist village, hoping that there will be follow-up by the village government.